Synchronous circadian voltage rhythms with asynchronous calcium rhythms in the suprachiasmatic nucleus - Enoki, Ryosuke (Proc Natl Acad Sci U S A, 2017)
The suprachiasmatic nucleus (SCN), the master circadian clock, contains a network composed of multiple types of neurons which are thought to form a hierarchical and multioscillator system. The molecular clock machinery in SCN neurons drives membrane excitability and sends time cue signals to various brain regions and peripheral organs. However, how and at what time of the day these neurons transmit output signals remain largely unknown. Here, we successfully visualized circadian voltage rhythms optically for many days using a genetically encoded voltage sensor, ArcLightD. Unexpectedly, the voltage rhythms are synchronized across the entire SCN network of cultured slices, whereas simultaneously recorded Ca(2+) rhythms are topologically specific to the dorsal and ventral regions. We further found that the temporal order of these two rhythms is cell-type specific: The Ca(2+) rhythms phase-lead the voltage rhythms in AVP neurons but Ca(2+) and voltage rhythms are nearly in phase in VIP neurons. We confirmed that circadian firing rhythms are also synchronous and are coupled with the voltage rhythms. These results indicate that SCN networks with asynchronous Ca(2+) rhythms produce coherent voltage rhythms.